Keabsahan Pengucapan Ijab Kabul Menurut Pandangan Ulama Aceh Singkil - Mahdalena Nasrun; Shalawati Shalawati (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
The pronunciation of Ijab Kabul is a phenomenon that the Aceh Singkil Ulama respond to in contradiction, so that it becomes an interesting material to be discussed according to the Aceh Singkil Ulama. The research question in this thesis is, How is the legal consent in marriage according to the views of the Aceh Singkil Ulama. And what is the legal basis used by the Aceh Singkil Ulama against the conditions for the validity of the consent and acceptance in the marriage contract. In the discussion of this thesis using (Field research). The data sources are primary data sources and secondary data sources. Based on the research results obtained show that; First, the pronunciation of Ijab Kabul is something that is easy to pronounce, not to be complicated for men and the Aceh Singkil Ulama make it easier to pronounce the Ijab Kabul for those who carry out this marriage, namely being able to use their own language (regional language), the most important thing is not to deviate from the meaning of marriage. (al-zawaj). Second, the legal basis regarding the pronunciation of consent and consent in Surah Az-Zariyat verse 49 "And we created everything in pairs so that you remember the greatness of Allah", that Allah has indeed promised in the Qur'an every creature on this earth was created. by God in pairs. And marriage is a job that is recommended for men who are able to get married so hasten to get married. And in the Qur'an it is also explained in Surah Al-Maidah verse 1 "O you who believe! Fulfill promises. Livestock is lawful for you, except what will be mentioned to you, by not making hunting lawful when you are in ihram (Hajj or Umrah). Verily, Allah sets the law according to what He wills." From the explanation above, it can be concluded that the pronunciation of marriage is something that is easy to say and a job that is recommended by Allah SWT.